Pengolahan Limbah Rumah Tangga Minyak Jelantah Menjadi Sabun Cair - Prabasari, Indira; Rineksane, Innaka Ageng (Universitas Muhammadiyah Yogyakarta, 2023)
Used cooking oil is dangerous for health, and its presence can pollute the environment if thrown away without processing it first. This training activity aims to provide insight and knowledge to the RT 03 Pasekan Lor area community about the dangers of used cooking oil and efforts to process used cooking oil into raw material for dishwashing soap. The activity aims to increase community knowledge and skills in using used cooking oil as a raw material for washing soap. This activity was carried out in several stages: (1) focus group discussion with RT 03 Pasekan Lor administrators to explore problems and formulate priority activities, (2) education on the dangers of used cooking oil for health and the environment, (3) training on making used cooking oil dish soap, and (4) evaluation monitoring activities related to participants' abilities in the independent practice of processing used cooking oil into dishwashing soap. Residents' awareness of not carelessly throwing away used cooking oil in the environment and their willingness to collect and process it into dishwashing soap increased after participating in the activity. The antimicrobial test results for dishwashing soap made from used cooking oil showed a total plate number of 6x102 colonies/ml and a pH of 7.4, meeting the SNI 4075-2:2017 standard. Organoleptic testing showed that the panelists liked the color, smell, viscosity, foam, and firmness of the training products. However, the product's bacterial inhibition test was still below that of commercial dishwashing soap products.